Perceived Ethical Climate and Forensic Accounting Services: Evidence From the Nigerian Public Sector - Nnedu Stanley Chinonso; Aggreh Meshack (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
It has been maintained that no matter the level of professional forensic accountants’ expertise, they would not achieve the goals of detecting and preventing fraud without the necessary supportive ethical climate. Therefore, this study investigated the effect of perceived ethical climate and the use of forensic accounting services for the detection and prevention of fraud in the Nigerian public sector. The study used data collected from the responses of 133 senior staff in the finance and accounts department of the six-area council in Abuja. The method of data analysis technique adopted for this study is multiple regression analysis with the aid of Statistical Package for Social Sciences (SPSS). The study found that perceived ethical climate (principle ethical climate and benevolence ethical climate) has a positive and significant effect on the application of forensic accounting services in the selected public sectors of Nigeria. The study concluded that one of the key elements influencing the use of forensic accounting services in the public sector is the perceived ethical climate. This study recommends that professional accountants should eschew the temptation to mislead and manipulate financial information, even while inaccuracies or differences of opinion regarding the applicability of forensic accounting services laws do exist.